Mycobacteria as evolutionary drivers of host innate immunity: insights from comparing experimental host models - Cortacans, Mariona; Cardona, Pere-Joan (Frontiers in Tuberculosis, 2025)
The genus Mycobacterium exerts a strong selective force, shaping the evolution and structure of innate immune systems across various hosts and revealing overarching, conserved principles of host defense. Despite their phylogenetic distance, amoebae, nematodes, insects, wax moth larvae, and zebrafish share fundamental innate immune strategies while also exhibiting key differences in tissue organization, immune complexity, and the presence or absence of adaptive immunity. This comparative review synthesizes insights from these systems to highlight both the conserved mechanisms that mycobacteria repeatedly exploit and the lineage-specific features that shape host susceptibility. Amoebae demonstrate ancient, cell-autonomous defenses, including nutritional immunity through metal trafficking (Nramp1/zinc intoxication) and membrane repair pathways (ESCRT/autophagy) against the ESX-1 system. Moving to metazoans, the importance of conserved signaling, such as the p38 MAPK (PMK-1) pathway in C. elegans, becomes evident, which M. marinum actively suppresses via VHP-1. In other invertebrates, such as Drosophila, integrated immunometabolism is present, in which disruption of the Akt–FOXO axis causes a conserved wasting syndrome, and Galleria mimics chronic TB pathology by forming granuloma-like structures with lipid-accumulating hemocytes and demonstrating innate immune priming. Larval zebrafish, which depend solely on innate immunity, show pathogen-driven granuloma formation and spread, with ESX-1 mediating pro-necrotic cell death and the Asc-dependent inflammasome contributing to restriction. Overall, these cross-species comparisons demonstrate how mycobacteria exploit foundational host mechanisms while revealing the evolutionary breadth and limits of innate immune strategies across the animal kingdom.